PENURUNAN AKTIVITAS BAKTERI PENGHASIL ENZYM DEKARBOKSILASE DENGAN PENAMBAHAN KITOSAN PADA IKAN TONGKOL (Euthynnus affinis) SEGAR - Gustiarti, Riski; Surti, Titi; Rianingsih, Laras (Jurnal Pengolahan dan Bioteknologi Hasil Perikanan, 2013)
Little tuna can easily spoile by bactery and enzyme activity which resulting scombrotoxin.Scombrotoxin was produce by histamine producing bacteria activity. Chitosan can be used to reducethe levels of histamine and also can be used as antibacterial and adsorben. The purpose of thisresearch is to determine the effect of chitosan solution addition to the decreating histamine level. Theresult of histamine content analysis showed that the addition of chitosan gave lower effect ofhistamine content of crushed little tuna. Histamine content value in a raw were 75,5 mg/100g ; 67,24mg/100g; 63,09 mg/100g ; 59,99 mg/100g at the level 0% (A0), 2% (A2), 3% (A3) and 5% (A5). Thereduction of histamine content showed highly significant difference between at control (A0) with 2%(A2); control (A0) with 3% (A3); control (A0) with 5% (A5); 2% (A2) with 3% (A3); 2% (A2) with 5%(A5) and 3% (A3) with 5% (A5) (P<0,01). The best quality of crush little tuna showed chitosanaddition at the level 5% with value TVBN Â±6,33 mg-N% dan TPC 1,0 x 102 kol/gr.